Hubungan Pengetahuan terkait Label Gizi dengan Kebiasaan Membaca Label Gizi pada Siswa SMA Al-Islam - Lutfia Puspaningtyas Islamiati; Sri Sumarmi (Media Gizi Kesmas, 2023)
Background: Just a few consumers who understand and use nutrition facts according to their function. This is due to lack of exposure and knowledge on consumer which is cause low level of awereness to read nutrition facts. Objectives: This study was to analyze the relationship between students' knowledge related to nutrition facts and reading nutrition facts habit carried out by students of SMA Al-Islam Krian. This study was an observational method using cross sectional design. Methods: Data collected through interviews using a questionnaire and analyzed using Kolmogorov Smirnov test and Spearman test. The sample was 250 students who were selected using a proportional random sampling from the student list. Results: The results showed that majority of students were sufficiently exposed to information related to nutrition facts (54.8%), sufficient nutrition facts knowledge (66%), and sufficient reading's nutrition facts habit (68.8%). There was no significant relationship between knowledge related to nutrition facts and reading nutrition facts habits with p-value 0.124.             Conclusions: It can be concluded that majority of students had been exposed to information related to nutrition facts, will had a good nutrition facts knowledge, and had a good reading nutrition facts habits, but there was no significant relationship between nutrition facts knowledge and reading nutrition facts habits.